(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
Preface to “The protection of minors between law and religion” ABSTRACT: “The best interest of the child” is exactly interpreted first of all as a "right of the child". Consequently, in case of conflict, the judge is given the power to balance between this right and other constitutionally protected ones. A test of acute difficulty and therefore significant concerns the ethically sensitive matter of religious beliefs and, in general, of superior duty. Furthermore, it is generally worrying that the struggle for the right to promote the freedom and dignity of the child (as, in general, of every person) stops in the face of security policies and, in particular, penitentiary policies, which characterize our era and which hinder listening of the viva vox Constitutionis.